Model Pembelajaran Multiple Intelegences dalam Meningkatkan Kinerja Guru PAUD - Khairiah Khairiah; Muridian Wijiati (IAIN Bengkulu, 2022)
Abstract: Early childhood education (ECCE) institutions have created difficulties implementing the required learning model to the quality of teacher performance. This paper aims to map and analyze multiple intelligence learning models in improving the performance of ECCE teachers. Using a descriptive qualitative method with a library research approach (literature study). The results show that there are still teachers who have not made updates in the learning process unless it is enough to repeat the material that has been taught the previous year, the teacher leaves the main tasks, functions, and responsibilities, only doing it for personal needs that are not clear. The teacher also does not attend on time or ends the lesson before the time is up, and the teacher has not been able to create comfortable classroom conditions, on the contrary, there are still teachers who abuse students psychologically, teachers are less creative, and the learning process is more academic by ignoring the development of children of play age. Pembelajaran model multiple intelegences terbukti dapat meningkatkan kinerja guru. Multiple intelligence-based learning is not only able to develop the intellectuality of each student, but can also help improve teacher performance and increase teacher creativity in designing learning based on the development of student intellectuality and creativity, thus causing awareness about the service of all the needs of students in a civilized and equitable manner. Thus, it can be suggested, that if you want the performance of ECCE teachers, then apply the multiple intelligences learning model perfectly.Keywords: Teacher Performance, Multiple Intelligences Learning Model, Early Childhood Education Institution Abstrak: Lembaga pendidikan anak usia dini (PAUD) telah menciptakan kesulitan menerapkan model pembelajaran yang menjadi persyaratan sebagai kualitas kinerja guru. Tujuan tulisan ini untuk memetakan dan menganalisis model pembelajaran mutiple intelegences dalam meningkatkan kinerja guru PAUD. Menggunakan metode kualitatif dsekriptif dengan pendekatan library reseach (studi kepustakaan). Hasilnya menunjukkan bahwa masih terdapat guru belum melakukan pembaharuan dalam proses pembelajaran kecuali merasa cukup dengan mengulang materi yang sudah diajarkan tahun sebelumnya, guru meninggalkan tugas pokok, fungsi dan tanggungjawabnya, hanya mengerjakan untuk keperluan-keperluan pribadi yang tidak jelas. guru juga tidak hadir tepat waktu atau mengakhiri pelajaran sebelum waktunya habis, guru belum mampu menciptakan kondisi kelas yang nyaman malah sebaliknya masih terdapat guru melakukan kekerasan secara psikologis kepada siswa, guru kurang kreatif, dan proses pembelajaran lebih banyak bersifat akademik dengan mengabaikan perkembangan anak usia bermain. Pembelajaran model multiple intelegences terbukti dapat meningkatkan kinerja guru. pembelajaan berbasis multiple intelegences tidak hanya mampu mengembangkan intelektualitas masing-masing peserta didik, melainkan juga dapat membantu meningkatkan kinerja guru, meningkatkan kreativitas guru dalam merancang pembelajaran yang berbasis pada pengembangan intelektualitas dan kreativitas siswa, sehingga menyebabkan adanya kesadaran tentang terlayaninya semua kebutuhan peserta didik secara beradab dan berkeadilan. Dengan demikian dapat disarankan, jika ingin kinerja guru PAUD, maka terapkanlah model pembelajaran multiple intelegences secara sempurna.Kata Kunci: Kinerja Guru, Model Pembelajaran Multiple Intelegences, Lembaga PAUD